"Gut Microbiota-Circadian Clock Axis" in Deciphering the Mechanism Linking Early-Life Nutritional Environment and Abnormal Glucose Metabolism. (27th August 2019) - Zhou, Liyuan; Kang, Lin; Xiao, Xinhua; Jia, Lijing; Zhang, Qian; Deng, Mingqun
Abstract : The prevalence of diabetes mellitus (DM) has been increasing dramatically worldwide, but the pathogenesis is still unknown. A growing amount of evidence suggests that an abnormal developmental environment in early life increases the risk of developing metabolic diseases in adult life, which is referred to as the "metabolic memory" and the Developmental Origins of Health and Disease (DOHaD) hypothesis. The mechanism of "metabolic memory" has become a hot topic in the field of DM worldwide and could be a key to understanding the pathogenesis of DM. In recent years, several large cohort studies have shown that shift workers have a higher risk of developing type 2 diabetes mellitus (T2DM) and worse control of blood glucose levels. Furthermore, a maternal high-fat diet could lead to metabolic disorders and abnormal expression of clock genes and clock-controlled genes in offspring. Thus, disorders of circadian rhythm might play a pivotal role in glucose metabolic disturbances, especially in terms of early adverse nutritional environments and the development of metabolic diseases in later life. In addition, as a peripheral clock, the gut microbiota has its own circadian rhythm that fluctuates with periodic feeding and has been widely recognized for its significant role in metabolism. In light of the important roles of the gut microbiota and circadian clock in metabolic health and their interconnected regulatory relationship, we propose that the "gut microbiota-circadian clock axis" might be a novel and crucial mechanism to decipher "metabolic memory." The "gut microbiota-circadian clock axis" is expected to facilitate the future development of a novel target for the prevention and intervention of diabetes during the early stage of life.